Driving and limiting factors of CH4 and CO2 emissions from coastal brackish-water wetlands in temperate regions - E. Chiapponi; S. Silvestri; D. Zannoni; M. Antonellini; B. M. S. Giambastiani (Biogeosciences, 2024)
Coastal wetlands play a fundamental role in mitigating climate change thanks to their ability to store large amounts of organic carbon in the soil. However, degraded freshwater wetlands are also known to be the first natural emitter of methane (CH4). Salinity is known to inhibit CH4 production, but its effect in brackish ecosystems is still poorly understood. This study provides a contribution to understanding how environmental variables may affect greenhouse gas (GHG) emissions in coastal temperate wetlands. We present the results of over 1 year of measurements performed in four wetlands located along a salinity gradient on the northeast Adriatic coast near Ravenna, Italy. Soil properties were determined by coring soil samples, while carbon dioxide (CO2) and CH4 fluxes from soils and standing waters were monitored monthly by a portable gas flux meter. Additionally, water levels and surface and groundwater physical–chemical parameters (temperature, pH, electrical conductivity, and sulfate concentrations of water) were monitored monthly by multiparametric probes. We observed a substantial reduction in CH4 emissions when water depth exceeded the critical threshold of 50 cm. Regardless of the water salinity value, the mean CH4 flux was 5.04 g<mspace width="0.125em" linebreak="nobreak"/>m-2<mspace linebreak="nobreak" width="0.125em"/>d-1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="47pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="b790de44938efcdc0f4fd466e647e96a"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-21-73-2024-ie00001.svg" width="47pt" height="15pt" src="bg-21-73-2024-ie00001.png"/></svg:svg> in freshwater systems and 12.27 g<mspace width="0.125em" linebreak="nobreak"/>m-2<mspace width="0.125em" linebreak="nobreak"/>d-1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="47pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="cb43a188c95fe696e3461dcd2324554f"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-21-73-2024-ie00002.svg" width="47pt" height="15pt" src="bg-21-73-2024-ie00002.png"/></svg:svg> in brackish ones. In contrast, when water depth was shallower than 50 cm, CH4 fluxes reached an average of 196.98 g<mspace linebreak="nobreak" width="0.125em"/>m-2<mspace width="0.125em" linebreak="nobreak"/>d-1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="47pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="c5c90d706a9f2a32c73f90e483d87b36"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-21-73-2024-ie00003.svg" width="47pt" height="15pt" src="bg-21-73-2024-ie00003.png"/></svg:svg> in freshwater systems, while non-significant results are available for brackish/saline waters. Results obtained for CO2 fluxes showed the same behavior described for CH4 fluxes, even though they were statistically non-significant. Temperature and irradiance strongly influenced CH4 emissions from water and soil, resulting in higher rates during summer and spring.